Sedimentary geochemical records of late Miocene-early Pliocene palaeovegetation and palaeoclimate evolution in the Ying-Qiong Basin, South China Sea - Ding, Wenjing; Hou, Dujie; Gan, Jun; Jiang, Lian; Zhang, Ziming; George, Simon C. (Marine geology, 2022)
The sedimentary geochemical records of palaeovegetation and palaeoclimate variations in late Miocene-early Pliocene sediments in the Ying-Qiong Basin, South China Sea have been studied using higher plant-derived biomarkers, palynological records, trace elements, and macerals. Aliphatic biomarkers including oleanane, des-A-oleanane, bicadinanes, and C19 tricyclic terpane, and the vitrinite content of the kerogen, show a remarkable decline in the input of the main angiosperms from about 8.2 to 2.7 Ma, corresponding to the deposition of the upper Huangliu Formation (late Miocene) to the lower Yinggehai Formation (early Pliocene). Aromatic parameters including retene/(retene + cadalene), 1,2,5-TMN/1,3,6-TMN, 1-MP/9-MP and 1,7-DMP/(1,3- + 3,9- + 2,10- + 3,10-DMP) suggest that the upper Huangliu Formation received a greater gymnosperm contribution than older Miocene formations. Trace element ratios (Rb/Sr and Zr/Rb) and the proportion of alginite-amorphous macerals in the shales indicate that a cooler, more arid climate with less seasonal precipitation occurred progressively from about 8.2–2.7 Ma, as also supported by higher abundances of Pinus and Alnus and decreasing proportions of ferns in the flora. Lesser input of terrigenous higher plants and the variation in vegetation types occurred during a cooling climate that was likely associated with a weaker East Asian summer monsoon and uplift of the northern Tibet-Plateau from about 8.5 Ma. •Palaeoclimate and palaeovegetation in Ying-Qiong Basin (S. China) reconstructed.•Higher gymnosperm/angiosperm and more Pinus in flora from 8.2–2.7 Ma.•From late Miocene to early Pliocene there was a cooling and drying climate.•Weakening East Asian summer monsoon occurred from 8.2–2.7 Ma.